THE WORLD’S SPIRIT AND THE CONCEPTUAL CHARACTER: TWO SUBJECTS OF THE HISTORY OF PHILOSOPHY AS THE PHILOSOPHICAL LOGIC - Гнатюк, Я. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
At the article are analyzed the sources of activity and the development of the history of philosophy. The main attention is addressed to the World’s spirit – the subject of the history of philosophy as the logic of conception and conceptual character – the subject of the history of philosophy as the logic of sense. The dialectical connection is grounded between the World’s spirit as absolute or universal subject and by conceptual character as the personal subject.